Genetic transformation of barley to modify expression of a 13-lipoxygenase - Sharma, Vijendra K. (Acta Biologica Szegediensis, 2005)
Immature scutella of barley were transformed with cDNA coding for a 13-lipoxygenase of barley (LOX-100) via particle bombardment. Regenerated plants were tested by PAT-assay, Western-analysis and PCR-screening. Immunocytochemical assay of T0 plants showed expression of the LOX cDNA both in the chloroplasts and in the cytosol, depending on the presence of the chloroplast signal peptide sequences in the cDNA. A few transgenic plants containing higher amounts of LOX-derived products have been found. These are the candidates for further analysis concerning pathogen resistance.